2015
DOI: 10.1111/wvn.12123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recording Food Intake Using Cell Phone Camera Pictures on Energy Intake and Food Choice

Abstract: Cell phone pictures may be an easy, relevant, and accessible method of diet self-monitoring when aiming at dietary changes. Future trials should combine this technique with healthy eating education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…A sub-theme that arose from survey responses was that the act of keeping a dietary record increased participants’ awareness of the food they ate. The findings of DBBB are mirrored in other studies where participants have reported increased awareness of foods or portion sizes consumed as a result of capturing images of food intake [ 40 ]. Participation in the DietBytes study may have created a teachable moment, by motivating women to consider dietary changes, and previous research has demonstrated that pregnancy is a time period when women may gain an increased awareness of their dietary intake [ 41 ] and be more receptive towards engaging in healthy eating behaviors [ 42 ].…”
Section: Discussionsupporting
confidence: 67%
“…A sub-theme that arose from survey responses was that the act of keeping a dietary record increased participants’ awareness of the food they ate. The findings of DBBB are mirrored in other studies where participants have reported increased awareness of foods or portion sizes consumed as a result of capturing images of food intake [ 40 ]. Participation in the DietBytes study may have created a teachable moment, by motivating women to consider dietary changes, and previous research has demonstrated that pregnancy is a time period when women may gain an increased awareness of their dietary intake [ 41 ] and be more receptive towards engaging in healthy eating behaviors [ 42 ].…”
Section: Discussionsupporting
confidence: 67%
“…Recent studies using RFPM conducted in pregnant women and preschoolers with obesity found that this method was not accurate in estimating energy intake compared to doubly labeled water [29,30]. Doumit et al conducted a cross-over study in college students, mostly of normal weight, to examine the effects of recording food intake from memory or with the aid of cell phone photos on energy intake and food choices [31]. They reported a nonsignificant trend for lower energy intake in the group using cell phone photos, suggesting increased awareness of food choice and portion size.…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 15 studies, four (27%) explicitly discuss dropout, reporting dropout rates of 7% (Epstein, Cordeiro, Bales, Fogarty, & Munson, 2014), 17% (Khovanskaya et al, 2013), 19% (Doumit et al, 2015), and 44% (Park et al, 2015). In nine studies (60%), dropout rates were not explicitly reported, but results imply that all participants completed the study (i.e., 0% dropout).…”
Section: Study Duration Dropout and System Usagementioning
confidence: 99%
“…Most systems provided anywhere, anytime access to data and feedback via a mobile app, whereas others used an application intended for desktop use (e.g., Collins, Cox, Bird, & Cornish-Tresstail, 2014;Doumit et al, 2015;Khovanskaya, Baumer, Cosley, Voida, & Gay, 2013). How and when data were accessible in the systems used by existing PI users was generally not reported on.…”
Section: Features and Use Of Evaluated Systemsmentioning
confidence: 99%
See 1 more Smart Citation